The Stories of Life: A few Notes on the Narrative Constructivism and Understanding Through Metaphor in the Debate Between Historical Studies and Evolutionary (Biosemiotic) Biology - Horský, Jan (Dějiny – teorie – kritika, 2016)
In current biosemiotics, semiosis and narrativity of life are often treated as pertaining to its defining features (Markoš). Narrative historical interpretations and metaphorical representations contained in them (Ankersmit) do not have precisely corresponding ontic counterparts. Nonetheless, both Ricoeur’s and Markoš’s conception of narration and metaphors should make it clear to historians and theorists of history that this does not imply that historical interpretations have no ontic counterparts. Within the context of historical sciences, one can claim that the ‘cultural objects’ of historians – even when viewed as products of the culture that is the object of the study – are much more transitory, and semiosis is much more ambivalent, than the ‘objects’ studied by biologists, if we take this term to mean the products of semiotic processes of life itself. In biosemiotics, the field where the meaning and reference of narratives of life are revealed is the morphological fi eld of shapes. That is then the correlate of the ‘field’ or ‘space’ of the spirit (Geist) or transcendental consciousness (Bewusstsein) known from the humanities. Th is correlation can be of interest to theorists of history from the point of view of cultural constructivism.